Cross-domain subcortical brain structure segmentation algorithm based on low-rank adaptation fine-tuning SAM - Yuan Sui; Qian Hu; Yujie Zhang (BMC Medical Imaging)
Abstract Purpose Accurate and robust segmentation of anatomical structures in brain MRI provides a crucial basis for the subsequent observation, analysis, and treatment planning of various brain diseases. Deep learning foundation models trained and designed on large-scale natural scene image datasets experience significant performance degradation when applied to subcortical brain structure segmentation in MRI, limiting their direct applicability in clinical diagnosis. Methods This paper proposes a subcortical brain structure segmentation algorithm based on Low-Rank Adaptation (LoRA) to fine-tune SAM (Segment Anything Model) by freezing SAM’s image encoder and applying LoRA to approximate low-rank matrix updates to the encoder’s training weights, while also fine-tuning SAM’s lightweight prompt encoder and mask decoder. Results The fine-tuned model’s learnable parameters (5.92 MB) occupy only 6.39% of the original model’s parameter size (92.61 MB). For training, model preheating is employed to stabilize the fine-tuning process. During inference, adaptive prompt learning with point or box prompts is introduced to enhance the model’s accuracy for arbitrary brain MRI segmentation. Conclusion This interactive prompt learning approach provides clinicians with a means of intelligent segmentation for deep brain structures, effectively addressing the challenges of limited data labels and high manual annotation costs in medical image segmentation. We use five MRI datasets of IBSR, MALC, LONI, LPBA, Hammers and CANDI for experiments across various segmentation scenarios, including cross-domain settings with inference samples from diverse MRI datasets and supervised fine-tuning settings, demonstrate the proposed segmentation algorithm’s generalization and effectiveness when compared to current mainstream and supervised segmentation algorithms.